Support Group Therapy sebagai Intervensi Pola Diet pada Lansia dengan Hipertensi - Sari, Ilma Widiya (Borobudur Nursing Review, 2025)
Hypertension is one of the most prevalent diseases among elderly. One of the key risk factors contributing to hypertension-related complications is an unhealthy dietary pattern. This study offers an updated approach by utilizing support group therapy as a social–educational intervention aimed at improving dietary habits among the elderly. Unlike conventional one-way educational methods, support group therapy emphasizes emotional support and shared experiences, thereby encouraging sustainable behavioral change. The purpose of this study was to determine the effect of support group therapy on dietary patterns among older adults with hypertension. A pre-experiment study using a one-group pre-test and post-test design was applied. The study population consisted of older adults and a total of 38 hypertensive older adults were selected using purposive sampling. The study collected data using a questionnaire and performed analysis with the parametric paired t-test. The findings revealed an increase in the mean dietary pattern score from 20.61 before the intervention to 31.23 after the intervention. Statistical analysis showed a significant effect of support group therapy on the dietary patterns of older adults (p = 0.000). Support group therapy is recommended to be routinely implemented in elderly posyandu as an educational and supportive strategy to improve adherence to healthy dietary practices and may be expanded on a broader scale to strengthen hypertension control among the elderly population.